Assessment of quantitative polymerase chain reaction for BCR–ABL1 transcripts in chronic myeloid leukaemia: Are improved outcomes in patients with e14a2 transcripts an artefact of technology?. (8th January 2022) - Dominy, Katherine M.; Claudiani, Simone; O'Hare, Matthew; Szydlo, Richard; Gerrard, Gareth; Foskett, Pierre; Foroni, Letizia; Milojkovic, Dragana; Apperley, Jane F.; Khorashad, Jamshid
Summary: The clinical outcome of chronic myeloid leukaemia patients has vastly improved since the introduction of tyrosine kinase inhibitor treatment, with a significant proportion of patients able to achieve treatment‐free remission. However, studies have shown that patients with the e13a2 transcript were less likely to achieve major molecular response compared to those with e14a2 transcripts. Most quantitative polymerase chain reaction (PCR) assays for detection of the BCR – ABL1 fusion gene do not differentiate between the two transcripts and we therefore hypothesised that technical bias linked to the qPCR assay could partially explain the discrepancy in outcomes. We designed an e14a2‐specific assay and identified no difference in results compared to an e13a2 standard assay. We then demonstrated that the commercial e14a2 standards were causing a significant overestimation of the e13a2 transcripts. Finally, we reviewed patient management after the qPCR values were corrected, using our new evaluation. We concluded that despite statistically significant differences in qPCR results, there was no impact on patient management or outcome. We conclude that, at least in our institution, it would be inappropriate to perform separate assays for patients with e13a2 or e14a2.